Genome-Wide Association Studies Provide Insights Into the Genetic Architecture of Seed Germination Traits in Maize - Li, Yuntong; Liang, Yameng; Liu, Meiling; Zhang, Qiyuan; Wang, Ziwei; Fan, Jinjuan; Ruan, Yanye; Zhang, Ao; Dong, Xiaomei; Yue, Jing; Li, Cong (Frontiers in Plant Science, 2022)
Seed germination is an important agronomic trait that affects crop yield and quality. Rapid and uniform seed germination traits are required in agricultural production. Although several genes are involved in seed germination and have been identified in Arabidopsis and rice, the genetic basis governing seed germination in maize remains unknown. Herein, we conducted a genome-wide association study to determine the genetic architecture of two germination traits, germination speed and consistency, in a diverse panel. We genotyped 321 maize inbred populations with tropical, subtropical, or temperate origins using 1219401 single-nucleotide polymorphism markers. We identified 58 variants that were associated with the two traits, and 12 of these were shared between the two traits, indicating partial genetic similarity. Moreover, 36 candidate genes were involved in seed germination, with functions including energy metabolism, signal transduction, and transcriptional regulation. We found that favorable variants had a greater effect on the tropical subpopulation than on the temperate. Accumulation of favorable variants shortened germination time and improved uniformity in maize inbred lines. These findings contribute significantly to understanding the genetic basis of maize seed germination and will contribute to the molecular breeding of maize seed germination.